Perancangan Sistem Informasi untuk Pengelolaan Tindakan Administratif Keimigrasian terhadap Warga Negara Asing pada Kantor Imigrasi - Intan Saravina; Cut Alna Fadhilla (Governance IT Adoption and Technology Advance, 2026)
The development of information technology has encouraged government institutions to improve the effectiveness and transparency of public services, including in the field of immigration. The Class II Immigration Office in Langsa plays an important role in the supervision and enforcement of immigration law against foreign nationals through the implementation of Immigration Administrative Actions (IAA). However, the previous management of IAA data was still carried out manually, which often resulted in delays and errors in recording and reporting processes. To address these issues, a web-based Immigration Administrative Action Information System was designed and developed using the Prototype Model methodology. The system was built using the PHP programming language, MySQL as the database, and implemented on a local XAMPP server. The implementation results indicate that the system is able to facilitate officers in inputting, managing, and compiling reports of administrative actions against foreign nationals in a fast and integrated manner. The simple user interface allows users to operate the system easily without requiring special training. The Class II Immigration Office in Langsa assessed the system as effective in improving administrative efficiency and supporting the digitalization of immigration services. The system is expected to be further developed by incorporating enhanced security features and automated report printing to sustainably support immigration operations.